2021
DOI: 10.1186/s12891-021-04145-4
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative deep venous thrombosis (DVT) after femoral neck fracture in the elderly, the incidence, timing, location and related risk factors

Abstract: Objective To investigate the epidemiologic characteristics of deep venous thrombosis (DVT) in elderly patients with femoral neck fracture. Methods Retrospective analysis was performed on elderly patients with femoral neck fractures admitted to two institutions from January 2016 to October 2019. Duplex ultrasonography (DUS) was used to detect DVT. Patients’ hospitalization medical records were retrieved to collect the data, which were related to dem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…Wang et al [ 14 ] reported that 83.6% of the DVTs were located in the injured extremity, 5.4% in the bilateral extremity, and 11.0% solely in the uninjured extremity in patients with isolated lower limb fracture. Niu et al [ 21 ] found that 76.1% of the DVTs solely involved the injured leg, 9.0% involved bilateral legs, and 14.9% solely involved the uninjured legs in the geriatric patients with a femoral neck fracture. However, some studies got slightly different results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [ 14 ] reported that 83.6% of the DVTs were located in the injured extremity, 5.4% in the bilateral extremity, and 11.0% solely in the uninjured extremity in patients with isolated lower limb fracture. Niu et al [ 21 ] found that 76.1% of the DVTs solely involved the injured leg, 9.0% involved bilateral legs, and 14.9% solely involved the uninjured legs in the geriatric patients with a femoral neck fracture. However, some studies got slightly different results.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the majority of the DVTs in closed patella fracture were distal DVT. In contrast with this, the rate of proximal DVT in the hip was much higher [ 8 , 11 , 21 , 23 ]. This demonstrated that the location of DVT may be associated with the fracture anatomical sites, the more proximal to the hip of the fracture site, the higher risk of the proximal DVT.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the physiological particularity of the elderly, the functional recovery of the bones of patients after fracture is often poor [ 5 ]. Statistics show that the elderly are prone to infection, deep vein thrombosis (DVT), pulmonary embolism, joint stiffness, and other complications after fracture [ 6 , 7 ]. Thus, to find an effective rehabilitation and nursing program is a vital task to improve hip joint dysfunction and reduce complications in elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…Among the 6 independent factors identified, most were repeatedly investigated in literature, such as delay to admission or DVT screening [ 10 , 17 – 19 ], higher BMI or obesity [ 18 , 19 ], peripheral vascular disease [ 19 ], reduced albumin [ 18 ] and elevated D-Dimer level [ 1 , 10 , 17 – 19 ]. The relatively prolonged time from injury to DVT examination (mean, 4.1 days) must be explain.…”
Section: Discussionmentioning
confidence: 99%
“…myocardial infarction or ischemic stroke or bleeding events [ 16 ], seriously complicating the surgical care. Despite the such clinical importance, existing studies on this topic are inadequate, reporting greatly variable prevalence rates of DVT and identified controversial risk factors without or limited adjustment for confounders [ 1 , 10 , 17 20 ], which are not necessarily applicable to populations in different settings.…”
Section: Introductionmentioning
confidence: 99%